Satellite communications systems engineering : atmospheric effects, satellite link design and system performance - Ippolito, Louis J., Jr. 1941- (Wiley, 2017)
Focuses on the important basic principles that are unique and timeless to satellite-based communications delivery systems The first edition of Satellite Communications Systems Engineering (Wiley, 2008) was written for those concerned with the design and performance of satellite communications systems employed in fixed point-to-point, broadcasting, mobile, radio navigation, data relay, computer communications, and related satellite-based applications. The rapid growth in satellite communications created a need for accurate information on both satellite communications systems engineering and the impact of atmospheric effects on satellite link design and system performance. It addressed that need for the first time in a single comprehensive source. This welcome second edition continues the basic premise and enhances the publication with the latest updated information and new technologies developed since the publication of the first edition. More in-depth treatments are included for the mobile satellite channel, satellite signal processing, on-board processing satellites, satellite orbits, transmission impairments, and propagation effects modeling and prediction. New chapters include interference mitigation in satellite communications, spectrum management for satellite communications, and high throughput satellites (HTS). Many of the updated tools and calculations are provided in a "handbook" form, with step-by-step procedures and all necessary algorithms in one place to allow direct calculations from one source. The book is based on graduate level satellite communications course material and has served as the primary text for electrical engineering Masters and Doctoral-level courses in satellite communications and related areas. Introductory to advanced level engineering students in electrical, communications and wireless network courses, and electrical engineers, communications engineers, systems engineers, and wireless network engineers looking for a refresher will find this essential text invaluable.